PENGARUH PEMBERIAN AIR KELAPA (Cocos nucifera L.) DAN AIR CUCIAN BERAS TERHADAP PERTUMBUHAN TANAMAN BAWANG DAUN (Allium fistulosum L.) - Nanda Raudhatul Jannah; Muslich Hidayat; Raudhah Hayatillah (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2024)
The scallion (Allium fistulosum L.) is a type of horticultural plant that is in great demand by the people. This study aims to identify the effects the growth of plants a scallion grow regulation (GR) with a combination of coconut water and leri water. The draft in this research is a random group rack consisting of 5 treatment by 5 repetition, the treatment consists of (P0 : control), (P1: 80% coconut water and 20% leri water), (P2 : 60% coconut water and 40% leri water), (P3: 40% coconut water and 60% leri water and (P4 : 20% coconut water and 80% leri water). Parameter observed in this study is leaf length number of leaves and a heavy wetness perpolybag. The result showed that the GR from the combination of coconut water and leri water affected the growth of leaf length, number of leaves and a heavy wetness perpolybag. The best GR combination treatment is the P4 treatment with a concentration of 20% coconut water and 80% rice washing water, namely leaf length (31.28 cm) and wet weight (5.8 g).